Effect of Some Insecticides on the Egg Parasitoid, Trichogramma evanescens Westwood (Hymenoptera: Trichogrammatidae) - Abdulhay, Hind Suhail; Rathi, Munther Hamza (Al-Nahrain Journal of Science, 2018)
In this study, the effects of three insecticides including: Fenvalerate, Thiacloprid and Fenoxycarb on egg parasitoid, Trichogramma evanescens were investigated. The toxicity of insecticide were tested using two laboratory tests: (a) direct spray on Ephestia cautella eggs containing the parasitoid for effects on parasitism and emergence of the adult parasitoids (b) adult parasitoid exposure to dry insecticide films residue in glass vials. All insecticides were prepared according to the manufacturer’s recommendations for field application. Results showed that these insecticides varied in toxicity and have different degrees of effect regarding the emergence and parasitism of the parasitoid. Fenoxycarb was non-toxic or low toxic to T. evanescen and did not affect immature stages development and adult emergence. Whereas, Fenvalerate was highly noxious to the parasitoid and significantly reduced the percentage of emergence and parasitism of T. evanescens developing in host eggs. The effects of Thiacloprid were slightly toxic to T. evanescens as it fell into the class 2 when parasitoids were directly exposed to chemical residues. While, Fenvalerate classified as moderately toxic and caused higher mortality than Fenoxycarb and Thiacloprid in both glass surface residues and direct spray of host eggs. Therefore, obtained data provided useful data for implementing both chemical and biological control strategies in integrated pest management.